(untitled) (GIST – Education and Learning Research Journal, 2024)
This qualitative case study examined teachers’ views on integrating Social-Emotional Learning (SEL) and its role in supporting Culturally Responsive Pedagogy (CRP). A total of 32 K-5th grade English as a Foreign Language (EFL) Uruguayan teachers completed a three-week online asynchronous professional development. Participants’ training focused on SEL principles, practices, and strategies for the English as a foreign language classroom. During the training, a three-scale rubric (0 - 3 points) served to formatively assess and provide feedback to the participants on completing weekly tasks. The evaluation examined the content of the teachers’ reflection and applications to practice. Feedback focused on how well teachers grasped the theoretical content and its integration. Once the training was completed, participants answered four open-ended questions in an online repository questionnaire. Findings document that after the intervention, the teachers perceived that students benefitted from learning about SEL and its implementation, and they came to believe that SEL principles need to become an integral part of instructional planning in Uruguay’s EFL classrooms.